Elution behavior of shortened multiwalled carbon nanotubes in size exclusion chromatography - Lee, Wonmok; Cho, Young Jin; Choi, Heung Ryul; Park, Hye Jin; Chang, Taihyun; Park, Min; Lee, Hyunjung (WILEY-V C H VERLAG GMBH, 2012)
We present a rigorous investigation on elution behaviors of ultrasonically shortened multiwalled carbon nanotubes in size-exclusion chromatography. The size separation of five carbon nanotube samples that underwent ultrasonic shortening for varying lengths of time revealed the existence of three kinds of carbon species: large nanotubes, small nanotubes, and amorphous carbon species. Separation of the three different carbon species was confirmed by SEM analyses on the fractionated eluates and also by light scattering/UV absorbance double detection. The chromatographic peak intensity ratio between the large and small nanotubes suggested an increased amount of small carbon nanotubes upon longer mechanical treatment time. The effect of the concentration of carbon nanotube dispersion on elution behavior was examined, and the elution volume of the shortened nanotubes was found to decrease upon dilution while that of the large nanotubes showed the opposite tendency. Unusual elution behaviors of the multiwalled carbon nanotubes were also observed by altering the flow rate, and these behaviors could be explained by the longer equilibration time taken for large nanotubes to access the pores of the packing materials and a possible morphology change of small carbon nanotubes.
Keywords: FIELD-FLOW FRACTIONATION; CAPILLARY-ELECTROPHORESIS; ELECTRONIC-STRUCTURE; MOLECULAR-WEIGHT; SEPARATION; LENGTH; PURIFICATION; NANOCOMPOSITES; EFFICIENCY; EMISSION